Republic of Congo : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Congo. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2019 Article IV Consultation with Congo discusses that the economic situation remains difficult, however, there are some initial signs of stability, and non-oil growth could turn positive for the first time since 2015. The political environment is stable, though there is discontent with government policies due in part to the authorities' limited engagement with the private sector and civil society. In the near term, the expansion of oil production explains most of the projected recovery in growth. However, peak oil production will be reached in 2020 rather than 2019 as initially expected. Non-oil growth is expected to pick up gradually as the government starts implementing its arrears clearance strategy, which could have a positive impact on business confidence and credit growth. The report recommends pursuing fiscal consolidation efforts and concludes the debt restructuring process for external commercial debt to restore fiscal sustainability. It is imperative to continue to implement measures to improve governance and tackle corruption, including through the adoption of operational decrees for the High Authority on Corruption and the Commission on Transparency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet